Malta : Financial Sector Assessment Program-Technical Note-Bank Resolution and Crisis Management. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note analyzes laws, policies, and procedures for bank failure mitigation and resolution, and for preparation and management of a financial crisis in Malta. It addresses the supervision of bank recovery plans, early intervention when problems are identified, resolution planning, resolution funding, and deposit insurance. Implementation of recovery planning requirements for banks remains a work in progress. Written policies and procedures should be adopted on the application of early intervention powers. While legal triggers and power for early intervention in problem banks are adequate, the powers in relevant legislation overlap substantially. Actions are needed to support the use of bank resolution powers, and to address weaknesses in the bank liquidation and insolvency framework. There is lack of clarity regarding the legal regime applicable to bank winding-up and insolvency, including as to the creditor hierarchy in liquidation. Impediments to implementation of the resolution tools are being identified and need to be addressed. Preparations need to be made for using the bridge institution resolution tool.